The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/antiox9070623
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, In Vitro Antioxidant Properties and Distribution of a New Cyanothiophene-Based Phenolic Compound in Olive Oil-In-Water Emulsions

Abstract: We synthesized and determined the antioxidant activity and distribution of a new cyanothiophene-based compound, N-(3-cyano-4,5,6,7-tetrahydrobenzo[b]thiophen-2-yl)-3,5-dihydroxybenzamide (SIM-53B), in intact stripped olive oil-in-water emulsion. The in vitro antioxidant properties of SIM-53B were evaluated and compared to those for Trolox and resveratrol. Addition of an emulsifier (Tween 20) creates a narrow region, the aqueous–oil interface, and the distribution of SIM-53B can be described by two partition co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Free-radical scavenging activity was evaluated employing the DPPH • and ABTS assays. In our previous study [32], we found that polyphenols are slow-reacting antioxidants; thus, we extended the incubation period in the DPPH and ABTS assays to 90 min. The 2,2-Diphenyl-1-picrylhydrazyl radical (DPPH • ) was dissolved in methanol (150 µL, 140 µM) and added to 150 µL methanol solution of the tested compound (62.5-500 µM), methanol (negative control) or α-tocopherol (positive control) in each well of a flat-bottomed 96-well microliter plate (TPP, Tissue Culture Test Plates).…”
Section: Antioxidant Activity Determined By Dpph • Abts and Cuprac Assaysmentioning
confidence: 99%
“…Free-radical scavenging activity was evaluated employing the DPPH • and ABTS assays. In our previous study [32], we found that polyphenols are slow-reacting antioxidants; thus, we extended the incubation period in the DPPH and ABTS assays to 90 min. The 2,2-Diphenyl-1-picrylhydrazyl radical (DPPH • ) was dissolved in methanol (150 µL, 140 µM) and added to 150 µL methanol solution of the tested compound (62.5-500 µM), methanol (negative control) or α-tocopherol (positive control) in each well of a flat-bottomed 96-well microliter plate (TPP, Tissue Culture Test Plates).…”
Section: Antioxidant Activity Determined By Dpph • Abts and Cuprac Assaysmentioning
confidence: 99%